FUCTIONAL OUTCOME OF ACUTE DISSEMINATED ENCEPHALOMYELITIS IN CHILDREN: Acute Disseminated Encephalomyelitis - Rehman, Muhammad Zia Ur; Sultan, Tipu; Ali, Shaila (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine functional outcome of acute disseminated encephalomyelitis in children and factorsaffecting outcome at The Children’s Hospital, Lahore.Study Design: Cross-sectional observational study.Place and Duration of Study: Department of Pediatric Neurology, The Children’s Hospital and Institute of ChildHealth, Lahore from Nov 2014 to Oct 2015.Material and Methods: Fifteen patients with acute disseminated encephalomyelitis fulfilling the inclusion criteriawere enrolled. Detailed history, examination, prior febrile illness and modified Rankin scale score for functionaldisability at presentation and discharge were recorded through study proforma. All patients underwent lumbarpuncture and neuroimaging. Data were analysed in SPSS (v.20) and Chi-square test was applied to find p-value.Results: Out of 15 patients, there was male predominance (10 male 66.7%) with mean age 7.4 ± 2.5 years.Encephalopathy 100% (n=15) followed by fever, fits 73.3% (n=11) and motor deficit 60% (n=9) were commonpresentation. About 46.7% (n=7) cases had prior febrile illness. MRI brain had >5 lesions in 86.7% (n=13) withsub-cortical area 93.3% (n=14) periventricular area 86.7% (n=13). Functional outcome was good in 80% (modifiedRankin scale of 2 or less at time of discharge). Consciousness level and disability score at presentation werestatistically significant factors affecting the outcome (p-value 0.004 & 0.002 respectively).Conclusion: Acute disseminated encephalomyelitis in children had variable clinical presentation. It has goodoutcome with level of consciousness and disability score being significant factors affecting outcome.